Diversidade e composição das comunidades de liquens crostosos em um gradiente altitudinal no Parque Nacional Serra de Itabaiana – SE. - Lima, Gabrielle Neris (2023)
Lichens are the result of the symbiotic association between a mycobiont (fungus) and a photobiont (algae and/or cyanobacteria). They disappear very quickly from regions where the environmental impact is high, as they accompany the temporal alterations of the vegetation. The present work seeks to study the variation of the structure of the lichen community in terms of composition, richness and abundance, in an altitudinal gradient in the main trail of the Parque Nacional Serra de Itabaiana (PARNASI) and to identify if there are changes in the lichen communities associated with altitude in the park. Two collections were carried out. To remove lichen thalli from the cortex of selected host phorophytes, a knife and hammer were used. The identification of the collected species was carried out according to specific bibliographies. For statistical analyses, analyzes were performed with Fischer's test (F), degrees of freedom (gl), Generalized Linear Model (GLM), Shannon (H') and Simpson (D), in addition to a cluster. Diversity indices did not differ significantly between individuals collected. The Shannon and Simpson diversity indices did not differ significantly among the collected individuals. Thus, the main objective of the work was to verify if the altitude influenced the composition of the species, which cannot be clearly verified, but which presents a tendency, therefore, more studies are necessary.